ANALISIS PERBANDINGAN PRESTASI BELAJAR MAHASISWA REGULER PAGI DAN REGULER SORE (Studi Kasus di Prodi Manajemen S1 FE Universitas Jenderal Achmad Yani) - Andri Irawan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
Research conducted by the authors aimed to determine the extent to which differences inoutcomes or achievement of learning from lectures that have been done by taking a sampleconsisting of 1 regular classes in the morning and 1 afternoon regular class with sample methodconsiderations . Type of statistics used are non- parametric statistics . The analytical tool used isTwo Independent Samples Test Analysis and Test Frequencies .Based on the results of data processing by using the Two Independent Samples showedthat Asymp . Sig ( 2 - tailed ) , the value 0.000 < 0.05 so stated Ha is accepted and it is concludedthat there are significant differences between the results of the final value obtained from the regularclassroom regular morning and afternoon . The test results of the analysis carried out frequenciescan be seen from the curve shows the average final grade regular classes are smaller than regularmorning afternoon ie 72.01 < 78.86 . Based on the discussion, it can be concluded that thedifference in the value of the end result of this could be due to the differences in character betweenstudents regular classroom regular morning and afternoon are different .